Three-Color Flow Cytometry Detection of Intracellular Cytokines in Peripheral Blood Mononuclear Cells: Comparative Analysis of Phorbol Myristate Acetate-Ionomycin and Phytohemagglutinin Stimulation - Baran, Jarołsaw (American Society for Microbiology, 2001)
The assessment of intracellular cytokines at the single-cell level by flow cytometry has recently become a potent tool in many areas of cell biology and in defining the role of cytokines in various human diseases. Three-color flow cytometry for detection of intracellular cytokines combined with simultaneous determination of lymphocytes (CD3(+) and CD4(+)) or monocytes (CD33(+) and CD14(+)) was used for comparison of phytohemagglutinin (PHA)-and phorbol myristate acetate (PMA)-ionomycin-induced production of intracellular cytokines in peripheral blood mononuclear cells (PBMCs) of healthy donors. We found that the number of PBMCs stained for tumor necrosis factor alpha and gamma interferon after 6 h of activation was higher when PMA-ionomycin was used for stimulation, while the frequencies of cells positive for interleukin 4 (IL-4) were similar for both stimulators. However, PMA-ionomycin stimulation caused prominent alterations of cell morphology and membrane expression of CD4 and CD14. In contrast, PHA did not cause downregulation of surface markers and resulted in less pronounced alterations in both forward and side scatter signals during flow cytometry analysis. Moreover, during 48 h of culture PHA stimulated tumor necrosis factor beta and IL-10 production, which was not observed when PMA-ionomycin was used. We conclude that the use of PHA for cell activation may limit in vitro artifacts and allow more precise analysis of intracellular cytokine production in various disease states.